Tinjauan Atas Prosedur Pengelolaan Persediaan Pada Proshop Klub Golf Bogor Raya - Shafa, Salsabila; Sari, Ervina Indri; Pardede, Robert Pius; Syarif, Rini (Program Vokasi dan LPPM IBI Kesatuan, 2023)
ABSTRACTInventory is one of the important current assets and has great value for the company's operations. This company does not have a lot of inventory, so there can be a shortage of inventory (stock out) and cannot meet customer requests. But if there is too much inventory (overstock) it will cause unsold goods and pile up in storage.The purpose of writing this research is to evaluate the management of merchandise inventory and to find out what constraints exist when managing inventory. Evaluation is carried out to find out whether inventory management has been carried out properly, also to find out whether obstacles in managing inventory can be overcome properly. The compiler made observations at the Bogor Raya Golf Club Proshop located in Bogor.The observation results show that the Bogor Raya Golf Club Proshop has managed its inventory quite well. Inventory management procedures have been carried out properly starting from submitting requests for goods, ordering goods, goods arriving, until the goods are sold. Even though inventory management at the Bogor Raya Golf Club Proshop has been going well, there are still a number of obstacles, such as late arrival of goods, unexpected requests and incompatibility of ordered goods.The results of the evaluation in this observation show that the Bogor Raya Golf Club Proshop must maintain efforts to manage its inventory, so that unwanted things do not occur which will harm the company. By maintaining inventory, the company does not need to incur costs for reordering or storage costs. Then if you see that the problem came from a supplier/vendor error, that way the company must be smart in choosing suppliers.Keywords: Management, Inventory of goods